Talking to the Enemy Track Two Diplomacy in the Middle East and South Asia - Kaye, Dalia Dassa (RAND Corporation, 2007)
This monograph examines security-related track two diplomacy efforts in the Middle East and South Asia, including how such efforts have socialized participants into thinking about security in more cooperative terms, and whether the ideas generated in track two forums have been acknowledged at the societal level or influenced official policy. Kaye concludes with suggestions on how to improve future track two efforts.